Adakah Hubungan antara Persepsi Kontrol Perilaku dan Niat dengan Perilaku Konsumsi Pornografi Online? - Ardi, Wintanti; Mubarokah, Kismi (Griya Widya: Journal of Sexual and Reproductive Health, 2024)
Background: Advances in internet technology have made it easy for students to find online pornography. The purpose of this study was to determine the relationship between perceived behavioral control and intention with online pornography consumption behavior among college students in Semarang City. Methodology: This research uses Quantitative method. With a cross sectional study design with an observational approach. Questionnaire research instrument. The sample calculation uses the Probability Sampling method with the Multi Stage Sampling approach. The collection technique uses Purposive Sampling via Google Form. With a sample of 399 respondents. Data analysis used the Spearman rho statistical test. Result: The results showed the characteristics of the respondents' gender, age, marital status, residence status, employment status and sexual orientation. Also, there is a relationship between perceived behavioral control and intention with online pornography consumption behavior. Recommendation: It is recommended that universities create communities to be aware and concerned about the dangers of pornography